Optimal efficacy of interferon-free HCV retreatment after protease inhibitor failure in real life. (October 2017) - Cento, V.; Barbaliscia, S.; Lenci, I.; Ruggiero, T.; Magni, C.F.; Paolucci, S.; Babudieri, S.; Siciliano, M.; Pasquazzi, C.; Ciancio, A.; Perno, C.F.; Ceccherini-Silberstein, F.; et al.
Abstract: Objectives: First-generation protease-inhibitors (PIs) have suboptimal efficacy in GT-1 patients with advanced liver disease, and patients experiencing treatment failure may require urgent retreatment. Our objective was to analyse the real-life efficacy of interferon (IFN)-free retreatment after PI-failure, and the role of genotypic-resistance-testing (GRT) in guiding retreatment choice. Methods: In this multi-centre observational study, patients retreated with IFN-free regimens after first-generation PI-failure (telaprevir-boceprevir-simeprevir) were included. Sustained-virological-response (SVR) was evaluated at week 12 of follow-up. GRT was performed by population-sequencing. Results: After PI-failure, 121 patients (cirrhotic = 86.8%) were retreated following three different strategies: A) with 'GRT-guided' regimens ( N = 18); B) with 'AASLD/EASL recommended, not GRT-guided' regimens ( N = 72); C) with 'not recommended, not GRT-guided' regimens ( N = 31). Overall SVR rate was 91%, but all 18 patients treated with 'GRT-guided' regimens reached SVR (100%), despite heterogeneity in treatment duration, use of PI and ribavirin, versus 68/72 patients (94.4%) receiving 'AASLD/EASL recommended, not GRT-guided' regimens. SVR was strongly reduced (77.4%) among the 31 patients who received a 'not recommended, not GRT-guided regimen' (p <0.01). Among 37 patients retreated with a PI, SVR rate was 89.2% (33/37). Four GT-1a cirrhotic patients failed an option (C) simeprevir-containing treatment; three out of four had a baseline R155K NS3-RAS. All seven patients treated with paritaprevir-containing regimens reached SVR, regardless of treatment duration and performance of a baseline-GRT. Conclusion: Retreatment of PI-experienced patients can induce maximal SVR rates in real life. Baseline-GRT could help to optimize retreatment strategy, allowing PIs to be reconsidered when chosen after a RASs evaluation.